Improved antifungal activity of barley derived chitinase I gene that overexpress a 32 kDa recombinant chitinase in Escherichia coli host - Nida Toufiq (Brazilian Journal of Microbiology)
Abstract Agricultural crops suffer many diseases, including fungal and bacterial infections, causing significant yield losses. The identification and characterisation of pathogenesis-related protein genes, such as chitinases, can lead to reduction in pathogen growth, thereby increasing tolerance against fungal pathogens. In the present study, the chitinase I gene was isolated from the genomic DNA of Barley (Hordeum vulgare L.) cultivar, Haider-93. The isolated DNA was used as template for the amplification of the ∼935 bp full-length chitinase I gene. Based on the sequence of the amplified gene fragment, class I barley chitinase shares 93% amino acid sequence homology with class II wheat chitinase. Interestingly, barley class I chitinase and class II chitinase do not share sequence homology. Furthermore, the amplified fragment was expressed in Escherichia coli Rosetta strain under the control of T7 promoter in pET 30a vector. Recombinant chitinase protein of 35 kDa exhibited highest expression at 0.5 mM concentration of IPTG. Expressed recombinant protein of 35 kDa was purified to homogeneity with affinity chromatography. Following purification, a Western blot assay for recombinant chitinase protein measuring 35 kDa was developed with His-tag specific antibodies. The purified recombinant chitinase protein was demonstrated to inhibit significantly the important phytopathogenic fungi Alternaria solani, Fusarium spp, Rhizoctonia solani and Verticillium dahliae compared to the control at concentrations of 80 µg and 200 µg.